Mathematics Education in Tunisia during the French Occupation Based On Cultural Historical Activity: A Historical-Analytical Study - Kouki , Rahim; Sammar, Mayada Khalili (Dirasat: Human and Social Sciences, 2024)
Objectives: This study addresses the development of mathematics education in Tunisia during the French occupation (1881-1912) from a historical aspect. This study highlights the factors that affected the development of mathematics education in Tunisia. The study also presents a detailed review of the assumptions and concepts of the cultural-historical activity theory [CHAT]. Since this theory considered a comprehensive framework for understanding the interactions between human and material elements in any activity system. Methods: The method utilized in the current study is qualitative content analysis that employed in this study involves applying the concepts and assumptions of CHAT to interpret and understand the historical development of mathematics education in Tunisia. This suggests an analytical approach grounded in the principles of cultural-historical activity theory to uncover the dynamics and influences shaping the educational landscape during the specified period of French occupation. Results: The findings indicated the ability of CHAT to provide a comprehensive understanding and interpretation of the course of the development of mathematics education in Tunisia during the French occupation (1881-1912). Conclusions: Tunisians recognized the importance of modern sciences, especially mathematics education, despite the obstacles imposed by the French occupation. Educational reformers succeeded in establishing modern educational institutions and implementing effective teaching methods. Students exerted significant efforts to assimilate contemporary knowledge, particularly in mathematics and achieved success and excellence. The study recommended utilizing CHAT to explain the development of mathematics education and other modern sciences in different temporal and spatial contexts.